Effects of Vessel Distance and Sex on the Behavior of Endangered Killer Whales - Holt, Marla M.; Tennessen, Jennifer B.; Ward, Eric J.; Hanson, M. Bradley; Emmons, Candice K.; Giles, Deborah A.; Hogan, Jeffrey T. (Frontiers in Marine Science, 2021)
Accurate knowledge of behavior is necessary to effectively manage the effects of human activities on wildlife, including vessel-based whale-watching. Yet, the wholly aquatic nature of cetaceans makes understanding their basic behavioral ecology quite challenging. An endangered population of killer whales faces several identified threats including prey availability and disturbance from vessels and sound. We used bio-logging tags that were temporally attached to individuals of the endangered Southern Resident killer whale population to more fully understand their subsurface behavior and to investigate vessel effects on behavior, including foraging outcomesbehavior involving prey capture. We collected tag data over three field seasons in the waters surrounding the San Juan Islands, WA, U.S.A., corresponding to the core summer area of the critical habitat of the population. Here, we used hidden Markov models to identify latent behavioral states that include characterization of different foraging states from sound and movement variables recorded by the multi-sensor tags. We tested a number of vessel variables (e.g. vessel counts, distance and speed) on state transition probabilities, state occurrence and time spent within each behavioral state. Whales made fewer dives involving prey capture and spent less time in these dives when vessels had an average distance less than 400 yd (366 m). Additionally, we found both a sex and vessel distance effect on the state transition probabilities, suggesting that females and males respond differently to nearby vessels. Specifically, females were more likely to transition to a non-foraging state when vessels had an average distance less than 400 yd (366 m). A female’s decision to forego foraging states due to the close proximity of vessels with close vessels could have cascading effects on the ability to meet energetic requirements to support reproductive efforts. This is particularly concerning in an endangered population that is in decline. Our findings, suggesting that female killer whales are at greater risk to close approaches by vessels, highlight the importance of understanding sex-specific responses to disturbance. These findings can inform future management decisions seeking to preserve foraging opportunities and enhance recovery efforts relevant to many cetacean species, including vulnerable and endangered populations.